Pengaruh Lama Penyimpanan Ekstrak Etanol Daun Sirih Hitam (Piper betle L. var Nigra) Terhadap Aktivitas Antibakteri: The Effect of Storage Time Extract Etanol Black Betel Leaf (Piper betle L. var Nigra) To Antibacterial Activity - Falencia Ega Aprillia; Mirhansyah Ardana; Hadi Kuncoro (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Black Betel Leaf (Piper betle L. var Nigra) contains compounds that act as antibacterials, namely alkaloids, flavonoids, saponins, tannins, steroids and phenolic compounds. Acne or acne vulgaris is an inflammatory reaction in the sebaceous follicles, which is caused by the Propionibacterium acnes bacteria. This study aims to prove that black betel leaf (Piper betle L. var Nigra) has antibacterial activity and has a long-lasting effect on the ethanol extract of black betel leaf against propionibacterium acne. The method includes sample extraction with 70% ethanol and then followed by antibacterial testing with the well method. In addition, the extract was prepared into a test solution and stored for 7 days at room temperature. The results of antibacterial testing using well diffusion can be concluded that the ethanol extract of black betel leaves with a concentration of 5%, 10%, 15%, 20% has the ability to inhibit the growth of propionibacterium acne bacteria. The effect of the extract storage time on day 7 had the largest inhibition zone.